2021
DOI: 10.1177/1532673x211053221
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People Engage in Unlawful Political Protest? Examining the Role of Authoritarianism in Illegal Protest Behavior

Abstract: Prior research on individual-level drivers of protest has primarily focused on legal protest. However, less is known about what makes people engage in unlawful protest activities. Building upon previous literature on the collective action dilemma, socialization on violent and high-risk social movements, and political psychology, we expect that illegal protest frequency varies at different levels of authoritarianism. We explore the relationship between authoritarian values and illegal protest by analyzing a two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Gutting (2020), for instance, finds that protests against law enforcement leaders decreases support for protest movements among authoritarians. Other research shows that individuals exhibiting high levels of authoritarianism are less likely to engage in protests (Inguanzo, Mateos, and de Zuniga, 2022) and less likely to engage in collective action more generally (Weiner and Federico, 2017). Consequently, existing studies have suggested that the combination of authoritarians’ sensitivity to pandemic threats coupled with their obedience to authority translate into higher support for restrictive mitigation policies (Bochiccio et al, 2021; Manson, 2020; Peng, 2021).…”
Section: Authoritarian Disposition and Pandemic Responsesmentioning
confidence: 99%
“…Gutting (2020), for instance, finds that protests against law enforcement leaders decreases support for protest movements among authoritarians. Other research shows that individuals exhibiting high levels of authoritarianism are less likely to engage in protests (Inguanzo, Mateos, and de Zuniga, 2022) and less likely to engage in collective action more generally (Weiner and Federico, 2017). Consequently, existing studies have suggested that the combination of authoritarians’ sensitivity to pandemic threats coupled with their obedience to authority translate into higher support for restrictive mitigation policies (Bochiccio et al, 2021; Manson, 2020; Peng, 2021).…”
Section: Authoritarian Disposition and Pandemic Responsesmentioning
confidence: 99%